Spatial Modeling Of Proboscis Monkey (Nasalis larvatus) Habitat Suitability Using Maximum Entropy In Tabunganen District - Dita Mahalleni Dita Mahalleni; Selamat Riadi; Arif Rahman Nugroho; Wisnu Putra Danarto (International Journal of Health Engineering and Technology, 2026)
The proboscis monkey (Nasalis larvatus) is a primate endemic to Borneo Island that faces threats due to habitat degradation and fragmentation. This study aims to analyze environmental factors influencing the presence of proboscis monkeys and model their habitat suitability in Tabunganen District, Barito Kuala Regency. The study used 18 proboscis monkey presence points monitored by the South Kalimantan Natural Resources Conservation Agency in 2025 and seven environmental variables analyzed using the Maximum Entropy method. The model produced an Area Under Curve value of 0.936, indicating excellent predictive ability. Distance from rice fields contributed the largest contribution (64.7%), followed by distance from gardens (14.2%) and distance from rivers (9.3%). The modeling results indicate that most areas fall into the low suitability class, while habitats with moderate to high suitability are concentrated in mangrove areas, riparian vegetation, and areas adjacent to rivers. These findings can be used as a basis for habitat management and determining proboscis monkey conservation priorities in Tabunganen District.